The Lecturers and Students’ Voice about Digital Reading: Does it Influence the Students’ Reading Skill? - Andi Tenrisanna Syam; Dewi Furwana (Linguistics Initiative, 2023)
This research attempts to determine whether digital reading has the same effect as traditional reading on students’ reading skill and to explain the lecturers and the students’ perceptions of digital reading. The writer applied mixed-method research. Sixty students participated as a research sample. Ten lecturers were also involved in this research. The instruments of this research were reading tests, questionnaires, and structured interviews. Reading tests were analyzed by using SPSS 22.0. The questionnaires were analyzed quantitatively using Microsoft Excel, and the structured interview was analyzed qualitatively. The writer found that digital and traditional reading does not affect students’ reading skills. It was evidenced by the t-test value being higher than the alpha (0.40 > 0.05). In contrast to many lecturers’ opinions, students do not prefer digital reading because they need more explanations from their lecturer. Meanwhile, the lecturers revealed that digital reading is useful for ongoing virtual learning. They also were confident in their ability to employ these digital readings. Both lecturers and students agree that the availability of technological tools is the key constraint they must deal with. This research hoped to give meaningful information to the government so that online readers can be facilitated with high-quality online reading materials based on their needs, interests, and behavior.